ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI BALI TAHUN 2015-2019 - Sarlitawati, Ni Putu Ferbilia; Sri Budhi, Made Kembar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.12.TAHUN.2022DO - 10.24843/EEB.2022.v11.i12.p02, 2022)
The implementation of regional autonomy gives wider authority to regional governments to regulate their own regions according to their potential. Fiscal decentralization is a form of delegation of authority in order to support the implementation of regional autonomy. This study aims to analyze the factors that influence the economic growth of districts/cities in Bali Province in 2015-2019. The data used in this study were sourced from secondary data. The analytical technique used is panel data regression analysis with the E-Views 9 program. The results of the study show that local revenue, balancing funds, capital expenditures and labor simultaneously have a significant effect on the economic growth of districts/cities in Bali Province in 2015-2019. Partially Local Original Income, capital expenditures and labor have no significant effect on the economic growth of districts/cities in Bali Province. Meanwhile, the balancing fund has a positive and significant impact on the economic growth of districts/cities in Bali Province in 2015-2019